The Effect of Parental Guidance on Student Personality at the High School Level - Wiliya Novianti; Tuti Alawiyah; Devy Sekar Ayu Ningrum (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: The family serves as the primary social institution responsible for shaping character and behavioral traits, yet the extent to which parental guidance influences overall personality development remains inconsistent in existing literature. Objective: This study aims to analyze the effect of parental guidance on student personality at the high school level and determine the strength of the relationship and contribution between the two variables. Methods: Employing a quantitative approach with an ex post facto design, the study involved 27 high school students selected through a saturated sampling technique. Data were gathered via questionnaires and analyzed using normality tests, Pearson correlation, simple linear regression, and t tests. Results: Findings reveal that parental guidance exerts a positive and significant effect on student personality. However, the correlation between the variables is low, with parental guidance contributing 10% to student personality while the remaining 90% is driven by external factors such as social environment and personal experiences. Conclusion: Although parental guidance is an essential factor in fostering student personality, it is not the sole dominant determinant and must be complemented by supportive environmental influences. Contribution: This research expands the empirical literature in educational science and psychology while serving as a practical reference for parents and educators to optimize guidance strategies for secondary school students.